2012
DOI: 10.2106/jbjs.l.00019
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Leukocyte Concentration in Platelet-Rich Plasma for the Treatment of Tendinopathy

Abstract: The optimum composition of PRP for the treatment of tendinopathy has not been directly investigated. Persistent inflammation results in inferior repair with scar tissue. The present study indicates that in an animal model, WBC in PRP contributes to inflammatory cytokine production. Therefore, leukocyte-reduced PRP may be the optimum preparation to stimulate superior healing without scar tissue formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
271
6
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(291 citation statements)
references
References 44 publications
9
271
6
5
Order By: Relevance
“…Neutrophils have been shown to contribute to oxidative damage and impair the resolution of contraction-induced muscle injury in mice [14]. Leukocytes secrete cytokines and other mediators that increase catabolism by promoting inflammatory responses via tumor necrosis factor-alpha (TNF-alpha), interleukin-1 (IL-1), and by decreasing extracellular matrix synthesis [15]. Heightened catabolism is associated with decreased sheer/tensile strength of soft-tissue and has been correlated with decreased recovery and healing.…”
Section: Pathophysiology and Mechanisms Of Muscle Healingmentioning
confidence: 99%
“…Neutrophils have been shown to contribute to oxidative damage and impair the resolution of contraction-induced muscle injury in mice [14]. Leukocytes secrete cytokines and other mediators that increase catabolism by promoting inflammatory responses via tumor necrosis factor-alpha (TNF-alpha), interleukin-1 (IL-1), and by decreasing extracellular matrix synthesis [15]. Heightened catabolism is associated with decreased sheer/tensile strength of soft-tissue and has been correlated with decreased recovery and healing.…”
Section: Pathophysiology and Mechanisms Of Muscle Healingmentioning
confidence: 99%
“…Dragoo et al [21] showed that leukocyte-rich PRP had a greater inflammatory response relative to leukocyte-poor PRP at post-injection day 5, but there was no difference at day 14. McCarrel et al [22] demonstrated that leukocytereduced PRP had decreased levels of tumor necrosis factor alpha and interleukin 1 beta relative to standard PRP, highconcentration PRP, and concentrated-leukocyte PRP.…”
Section: Prp Duration Of Effectmentioning
confidence: 99%
“…Regarding the optimal concentration of the platelets in PRP for the tendon healing, some researchers reported in vitro studies. McCarrell demonstrated that the PRP at the platelets concentration of 1.2×10 6 /µL led to a paradoxical effect on collagen synthesis on the culture of horse tendons compared to the PRP at the intermediate concentration of the platelets, while also presenting an increase in inflammatory mediators 24 . Boswell also demonstrated that the PRP at the high platelets concentration reduced tendon metabolism and collagen synthesis in equine tendon culture 25 .…”
Section: Introductionmentioning
confidence: 99%